2013
DOI: 10.1523/jneurosci.1148-13.2013
|View full text |Cite|
|
Sign up to set email alerts
|

Fast Vesicle Transport Is Required for the Slow Axonal Transport of Synapsin

Abstract: Although it is known that cytosolic/soluble proteins synthesized in cell bodies are transported at much lower overall velocities than vesicles in fast axonal transport, the fundamental basis for this slow movement is unknown. Recently, we found that cytosolic proteins in axons of mouse cultured neurons are conveyed in a manner that superficially resembles diffusion, but with a slow anterograde bias that is energy-and motor-dependent (Scott et al., 2011). Here we show that slow axonal transport of synapsin, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 50 publications
(49 reference statements)
3
70
1
Order By: Relevance
“…KIF5B knockdown showed that proteasome dynamics have a partial dependency on kinesin-1 and are consistent with the idea that the 26S proteasome is 'hitch-hiking' on different cargos in order to move. Interestingly, our results fit a model in which cytosolic proteins are transported by different types of movement -including the contribution of vesicle carriers under fast axonal transport (Scott et al, 2011;Tang et al, 2013). Furthermore, by high-resolution imaging and single-particle tracking, we identified and characterized diffusive modes of transport and actively driven transport that mediate the distribution of proteasomes within axons.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…KIF5B knockdown showed that proteasome dynamics have a partial dependency on kinesin-1 and are consistent with the idea that the 26S proteasome is 'hitch-hiking' on different cargos in order to move. Interestingly, our results fit a model in which cytosolic proteins are transported by different types of movement -including the contribution of vesicle carriers under fast axonal transport (Scott et al, 2011;Tang et al, 2013). Furthermore, by high-resolution imaging and single-particle tracking, we identified and characterized diffusive modes of transport and actively driven transport that mediate the distribution of proteasomes within axons.…”
Section: Discussionsupporting
confidence: 63%
“…The movement of these and many cytosolic proteins has been suggested to depend on the interaction with fast motors for their stochastic movement (Scott et al, 2011). Recently, the fast movement of a carrier, now identified as moving vesicles, has been suggested to drive the anterograde slow axonal transport of the synapsin proteins, suggesting that there are many modes for the movement for soluble proteins (Tang et al, 2013). In this study, we tested whether the neuronal proteasome complex relies on different axonal transport mechanisms for movement in axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We transfected α-syn null neurons with VN/VC:α-syn (or Venus:α-syn) and visualized the entry of newly-synthesized (somatically-derived) fluorescent molecules into boutons (4-5 hours after transfection), adopting an imaging strategy that we recently developed ([21], see schematic in fig. 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…Cultured α-syn −/− neurons were co-transfected with VN/VC:α-syn's (or Venus:α-syn) + soluble mCherry, and kinetics of initial α-syn entry and synaptic accumulation was evaluated by long-term imaging (see “results” and [21] for more details).…”
Section: Figurementioning
confidence: 99%